Factors Related To Infant Mortality Rate - Desi Tri Astuti; Siti Chunaeni; Ayuningtiyas Ayuningtiyas (Midwifery and Nursing Research, 2022)
Background: Infant mortality rate are infants who death that were 0 to 365 days old. In Indonesia, the infant mortality rate are 24/1000 live births. Risk factors for infant mortality rate were factors from the baby and the mother. Maternal characteristics are a factors in infant mortality rate that can be controlled with early intervention, so it is necessary to know what factors influence infant mortality. The purpose of the study was to analyze the factors related to infant mortality rate in Puskesmas Pejawaran Methods: This research was conducted in Puskesmas Pejawaran. This is an case control study. The population taken is 1 : 1 by the subjects of 17 cases and 17 babies born alive so that there are 34 respondents. The sampling technique used arandom sampling technique. The study used secondary data, The data analysis used in this study was the chi square test. Result: There is a relationship between the age of the respondent and infant mortality rate in Puskesmas Pejawaran, there is no relationship between parity, pregnancy interval and the level of education of the respondent’s age with mother’s age with infant mortality. Mothers aged 35 years who gave birth to babies were 4.4 times more likely to give birth to stillbirth. Conclusion: There is a relationship between respondent’s age with mother’s age and infant mortality rate in Puskesmas Pejawaran, there is no relationship between parity, pregnancy interval and the level of education of the respondent's age with infant mortality rate.